LAMPUNG PROVINCE ADOPTION OF SUSTAINABLE DEVELOPMENT GOALS 05 (GENDER EQUALITY) AS GLOBAL NORMS INTO LOCAL ORDER - Darmastuti, Ari; Inayah, Astiwi; Simbolon, Khairunnisa (Journal of Social Political Sciences, 2024)
This research aimed to analyze the efforts made by the Lampung Provincial Government in adopting the Sustainable Development Goals (SDGs) Goal 5 (Gender Equality) values ​​into the local order. The research used a qualitative descriptive method with qualitative data collection techniques. The results of this research showed that the Lampung Provincial Government has made various efforts to adopt the SDGs Goal 5 values ​​into the local order. These efforts such as made gender equality to be one of the prioritized focus by incorporating women's empowerment into the third mission of Lampung Province which was then realized in the form of work promises; implementing gender mainstreaming down to districts, city and village levels; implementing programs and activities for the development of women empowerment and child protection; creating and implementing relevant regional innovations in the field of women's empowerment and child protection and population control in Lampung Province; signing of a joint commitment; to advocating for policies related to gender mainstreaming. These efforts indicated that gender equality norms have reached a stage of internalization in the dynamics of international norms. Even the internalization has touched the people of regencies/cities and villages in Lampung Province. Nevertheless, the Lampung Provincial Government continues to face opportunities and challenges in adopting the SDGs Goal 5 values. Keywords: SDGs; gender equality; global norm; local order